Shared decision-making in chronic kidney disease: A retrospection of recently initiated dialysis patients in Germany - Robinski, Maxi; Mau, Wilfried; Wienke, Andreas; Girndt, Matthias (Patient education and counseling, 2016)
•PD patients retrospectively rate SDM more positively than do HD patients.•PD patients indicate the desire of independence as dominant reason for treatment choice.•HD patients were subject to medical decisions or wanted to rely on medical support.•Patients’ SDM rating correlates positively with their treatment satisfaction. To compare differences in shared decision-making (SDM) and treatment satisfaction (TS) between haemodialysis (HD) and peritoneal dialysis (PD) patients. 6–24 months after initiation of dialysis, we surveyed 780 patients from throughout Germany (CORETH-project) regarding SDM, the reason for modality choice and TS. Data were compared between two age-, comorbidity-, education-, and employment status-matched groups (n=482). PD patients rated all aspects of SDM more positively than did HD patients (total score: MPD=84.6, SD=24.1 vs. MHD=61.9, SD=37.3; p≤0.0001). The highest difference occurred for the item “announcement of a necessary decision” (delta=1.3 points on a 6-point Likert-scale). PD patients indicated their desire for independence as a motivator for choosing PD (65%), whereas HD patients were subject to medical decisions (23%) or wanted to rely on medical support (20%). We found positive correlations between SDM and TS (0.16≤r≤0.48; p≤0.0001). Our findings increase awareness of a participatory nephrological counseling-culture and imply that SDM can pave the way for quality of life and treatment success for dialysis patients. Practitioners can facilitate SDM by screening patient preferences at an early stage, being aware of biases in consultation, using easy terminology and encouraging passive patients to participate in the choice.